Double-layer composite polyimide film as well as preparation method and application thereof
By adopting a multi-layer structure, a film composed of polyimide composite film and a high-insulating nanosheet, the problems of low dielectric performance and insufficient energy storage density in high temperature and high pressure environments are solved. The dielectric constant and breakdown strength are improved, and the energy storage performance is improved.
Patent Information
- Application Number
- CN202411094607.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-10
- Publication Date
- 2025-02-18
AI Technical Summary
The existing polymer films have low dielectric performance in high temperature and high pressure environments and are insufficient energy storage density, making it difficult to meet the needs of efficient energy storage.
Designed with a multi-layer structure, the first layer is a polyimide composite film, and the second layer is a film composed of high-insulating nanosheets and polymer adhesives, through interface barriers and wide band gap nanosheets Obstruct breakdown path extension and carrier delivery.
The dual improvement of dielectric constant and breakdown strength is achieved, and the energy storage performance and operation efficiency of the film in high temperature and high pressure environments are improved.
Smart Images

Figure CN119463718A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of dielectric film capacitor related materials, and in particular relates to a multilayer composite film and a preparation method and application thereof. Background Art
[0002] In today's energy-rich world, the way to use and store energy is also advancing with the times. The most common energy storage devices require dielectric films with excellent dielectric properties. Energy conversion is particularly important. Converting sustainable energy such as wind energy and hydropower into convenient and practical electrical energy requires devices that can adapt to high temperature and high pressure environments, and the same is true for energy storage devices. However, the dielectric properties of simple polymer films are relatively low. In order to adapt to high temperature and high pressure environments, it is necessary to improve high-temperature energy storage performance. In order to adapt to long-distance transportation and use, it is necessary to increase energy storage density. These research directions are very necessary based on the current imbalance in national energy use. In the foreseeable future, human energy consumption will increase, so converting renewable energy into directly usable electrical energy and storing it is an urgent problem to be solved. Therefore, the requirements for energy storage are becoming more and more stringent, and more and more efficient energy storage devices are needed.
[0003] By optimizing various aspects of the performance of dielectric composite films, the overall performance of electronic devices on the current market can be improved, their energy storage performance and operating efficiency can be improved, and the development of different industries can be promoted. At present, the dielectric constant can be improved by adding filler components to the polyimide-based matrix and mixing them with high dielectric performance materials such as barium titanate (BT), but this is at the expense of reducing the breakdown field strength. Therefore, in order to make up for this, dispersed boron nitride nanosheets (BNNSs) and other components are added to increase the breakdown field strength. Compared with the traditional blending process, the multilayer film can effectively hinder the transfer of carriers and inhibit the extension of the breakdown path due to the interaction of the interlayer interface, and has a higher breakdown strength, thereby improving the performance of the dielectric material. Summary of the invention
[0004] In response to the above problems, the present invention provides a double-layer composite film and a preparation method and application thereof, which adopts a multi-layer structure to construct an interface barrier and introduces high-insulation nanosheets with a wide bandgap in the second layer to further hinder the extension of the breakdown path and the transfer of carriers, thereby achieving a dual increase in the dielectric constant and breakdown strength.
[0005] The invention provides a double-layer composite film, which comprises: a first layer of polyimide composite film and a second layer of adhesive film.
[0006] The multilayer composite film as described above, wherein the high dielectric nanoparticles are barium titanate, titanium dioxide, barium strontium titanate, and calcium copper titanate.
[0007] The multilayer composite film as described above, wherein the second film layer is composed of insulating nanosheets and a polymer adhesive.
[0008] The multilayer composite film as described above, wherein the insulating nanosheets are one or more of boron nitride, aluminum oxide, mica, and montmorillonite.
[0009] The multi-layer composite film as described above, wherein the second layer of polymer adhesive is one or more of low-viscosity epoxy adhesive and polydimethylsiloxane.
[0010] The multi-layer composite film as described above, wherein the thickness of the polyimide composite film is 5 μm-15 μm.
[0011] The multi-layer composite film as described above, wherein the thickness of the second layer is 0.5 μm-5 μm.
[0012] The present invention also provides a method for preparing a multilayer composite film, which comprises the following steps:
[0013] The first step is the preparation of high dielectric nanoparticle / polyimide composite film;
[0014] A certain amount of high dielectric nanoparticles is added to an organic solvent A for ultrasonic dispersion to obtain a uniform mixed solution B; after adding ODA, the mixture is stirred evenly and then ultrasonicated for 1 hour, and finally PMDA is added for stirring and reaction to obtain a mixed solution C, the mixed solution is placed in a vacuum drying oven to evacuate the vacuum, the solution is poured onto a glass plate and coated with a scraper to form a thin film, and finally placed in an electric constant temperature blast drying oven and set to 130°1h, 180°1h, 230°1h, 280°1h, 300°0.5h, and run the drying and curing procedures; the obtained film thickness is between 5-15μm;
[0015] Step 2: Preparation of double-layer film:
[0016] A certain mass of insulating nanosheet powder is ultrasonically dispersed in an organic solvent D to obtain a uniform mixed solution E. A certain mass of adhesive component a is then added to solution E, and after ultrasonic dispersion, a fixed proportion of adhesive component b is added, and ultrasonic dispersion is continued until uniform dispersion, and the solvent is heated and stirred continuously to evaporate, and the mixture is placed in a vacuum drying oven for evacuation to obtain a mixed solution F; a polymer film is spread flat on a clean glass plate, a certain volume of the above solution F is added dropwise on the surface of the film, and the solution is evenly coated on the bottom polymer film by a casting method to obtain a double-layer film, which is then placed in an oven at 50-80°C for curing for 24 hours.
[0017] In the preparation method as described above, in the first step, the organic solvent A is one of isopropanol, dimethylacetamide and N-methylpyrrolidone.
[0018] In the preparation method as described above, in the second step, the size of the insulating nanosheets is 2-15 μm.
[0019] In the preparation method as described above, in the second step, the organic solvent D is one of acetone and tetrahydrofuran.
[0020] The preparation method as described above, wherein the vacuum degassing time is 5 to 15 minutes. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Cross-sectional SEM image of the multilayer composite film prepared in the example;
[0022] Figure 2 This is a performance comparison table of the multilayer composite films (abbreviated as PI, 10-BT / PI, 20-BT / PI, BNNSs@BT / PI) prepared in Comparative Examples 1 to 3 and Examples. DETAILED DESCRIPTION
[0023] To make the purpose, technical solution and advantages of the present invention more clear, the embodiments of the present invention are described in detail below. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other arbitrarily without conflict.
[0024] Example:
[0025] The present invention provides a preparation method of a double-layer polyimide composite film and related applications. The multi-layer film comprises a first layer of polyimide composite high-dielectric filler film and a second layer of adhesive composite high-insulation filler film.
[0026] (1) Preparation of high dielectric nanoparticle / polyimide composite films
[0027] Weigh a certain mass of nano BT particles and add them to the solvent N,N-dimethylacetamide. Ultrasonicate in an ultrasonic cleaner for 0.5 to 2 hours until the nano BT particles at the bottom of the beaker are evenly dispersed. After adding ODA, stir evenly and continue ultrasonicating for 0.5 to 2 hours. Finally, add PMDA (the molar mass ratio of ODA to PMDA is 1: (1 to 1.1), and the solid content is 10 to 20%) and stir for 6 to 24 hours to maintain the dispersion of BT particles. Take it out and continue ultrasonicating for 0.5 to 2 hours. Put the obtained mixed solution into a vacuum drying oven and vacuum it for 2 to 10 minutes. Repeat twice to ensure that the bubbles in the solution are eliminated. Then pour the solution on a glass plate and use a scraper to scrape it into a film of about 0.01 to 0.05 mm. Finally, put it into an electric constant temperature blast drying oven and set the program of 130°1h, 180°1h, 230°1h, 280°1h, 300°0.5h and run. The thickness of the obtained BT / PI film is between 5 and 15μm. After taking out the glass plate, soak it in water to remove the film, and then dry it to obtain the formed BT / PI composite film.
[0028] Preferably, the high dielectric nanoparticles are barium titanate (BT), titanium dioxide (TO), barium strontium titanate (BST), calcium copper titanate (CCTO), and more preferably barium titanate.
[0029] Preferably, the insulating nanosheet is one or more of two-dimensional nanosheets such as boron nitride (BN), aluminum oxide (AO), mica (Mica), montmorillonite (MMT), etc., and is more preferably boron nitride.
[0030] Preferably, the second layer of polymer adhesive is one or more of low-viscosity epoxy adhesive and polymer adhesive in polydimethylsiloxane (PDMS), and more preferably low-viscosity epoxy adhesive.
[0031] Preferably, the thickness of the polyimide composite film is 5 μm-15 μm, more preferably 8 μm-12 μm.
[0032] Preferably, the second layer has a thickness of 0.5 μm-5 μm.
[0033] Preferably, the ultrasound duration is 0.8 to 1.2 hours.
[0034] Preferably, the solid content is 12-18%.
[0035] Preferably, the stirring time is 10 to 16 hours.
[0036] Preferably, the vacuuming time is 3 to 7 minutes.
[0037] Preferably, the film thickness of the blade coating is 0.01 to 0.02 mm.
[0038] Preferably, the thickness of the BT / PI film is between 8 and 12 μm.
[0039] (2) Preparation of double-layer film:
[0040] Weigh a certain amount of exfoliated BNNSs nanosheets and put them into an organic solvent solution (the mass fraction of BNNSs in the BNNSs / BT / PI system is 1-20wt%), add epoxy resin component a and ultrasonicate for 0.5-2h, then add epoxy resin component b and ultrasonicate for 0.1-1h to obtain a mixed solution for spin coating. Take out the BT / PI composite film prepared above, cut a composite film of appropriate size on a glass sheet, spin coat the prepared BNNSs solution in a desktop coating machine, and then put the glass sheet into an oven at 50-80℃ for curing for 12-24h.
[0041] Preferably, the organic solvent is one of acetone and tetrahydrofuran, more preferably acetone.
[0042] Preferably, the mass fraction of BNNSs in the BNNSs / BT / PI system is 5 to 15 wt %.
[0043] Preferably, after adding the epoxy resin component a, ultrasonic treatment is performed for 0.5 to 1 hour.
[0044] Preferably, the epoxy resin b component is added and ultrasonicated for 0.1 to 0.5 hours.
[0045] Preferably, the oven curing temperature is 55-65°C.
[0046] Preferably, the curing time is 18 to 24 hours.
[0047] Comparative Example 1:
[0048] After adding ODA to the solvent N,N-dimethylacetamide and stirring evenly, PMDA (ODA to PMDA molar mass ratio is 1: (1-1.1), solid content is 10-20%) is gradually added and stirred for reaction. The obtained mixed solution is placed in a vacuum drying oven and vacuumed for 2-10 minutes, repeated twice to ensure that the bubbles in the solution are eliminated, and then the solution is poured on a glass plate and scraped with a scraper to form a film of about 0.01-0.05 mm, and finally placed in an electric constant temperature blast drying oven and set to 130°1h, 180°1h, 230°1h, 280°1h, 300°0.5h program, and run. The thickness of the obtained pure PI film is between 5 and 15μm. After taking out the glass plate, soak it in water to remove the film, and after drying, the formed PI film can be obtained.
[0049] Comparative Example 2:
[0050] Weigh a certain mass of nano BT particles (mass fraction of 10%) and add them to the solvent N,N-dimethylacetamide. Ultrasonicate in an ultrasonic cleaner for 0.5 to 2 hours until the nano BT particles are evenly dispersed at the bottom of the beaker. After adding ODA, stir evenly and continue ultrasonicating for 0.5 to 2 hours. Finally, add PMDA (ODA to PMDA molar mass ratio is 1: (1 to 1.1), solid content is 10 to 20%) and stir for 6 to 24 hours to maintain the dispersion of BT particles. Take out and continue ultrasonicating for 0.5 to 2 hours. Put the obtained mixed solution into a vacuum drying oven and vacuum for 2 to 10 minutes, repeat twice to ensure that the bubbles in the solution are eliminated, then pour the solution on a glass plate and use a scraper to scrape it into a film of about 0.01 to 0.05 mm, and finally put it into an electric constant temperature blast drying oven and set the program of 130°1h, 180°1h, 230°1h, 280°1h, 300°0.5h, and run. The thickness of the obtained BT / PI film is between 5 and 15 μm. After taking out the glass plate, soak it in water to remove the film, and after drying, a formed 10-BT / PI composite film can be obtained.
[0051] Comparative Example 3:
[0052] Weigh a certain mass of nano BT particles (mass fraction of 20%) and add them to the solvent N,N-dimethylacetamide. Ultrasonicate in an ultrasonic cleaner for 0.5 to 2 hours until the nano BT particles are evenly dispersed at the bottom of the beaker. After adding ODA, stir evenly and continue ultrasonicating for 0.5 to 2 hours. Finally, add PMDA (ODA to PMDA molar mass ratio is 1: (1 to 1.1), solid content is 10 to 20%) and stir for 6 to 24 hours to maintain the dispersion of BT particles. Take out and continue ultrasonicating for 0.5 to 2 hours. Put the obtained mixed solution into a vacuum drying oven and vacuum for 2 to 10 minutes, repeat twice to ensure that the bubbles in the solution are eliminated, then pour the solution on a glass plate and use a scraper to scrape it into a film of about 0.01 to 0.05 mm, and finally put it into an electric constant temperature blast drying oven and set the program of 130°1h, 180°1h, 230°1h, 280°1h, 300°0.5h, and run. The thickness of the obtained BT / PI film is between 5 and 15 μm. After taking out the glass plate, soak it in water to remove the film, and after drying, a formed 20-BT / PI composite film can be obtained.
[0053] Dielectric property test: Copper electrodes were first deposited on both sides of the film using a high vacuum resistance evaporation coating machine, and then the film coated with copper electrodes was placed in a precision impedance analyzer (Novocontrol Technologies BDS 40) and the copper electrodes were clamped with a clamp. The multilayer composite materials prepared in Examples 1 to 3 and Comparative Example 1 were tested at room temperature at 1 Hz to 10 6 Dielectric properties in the Hz range, the specific comparison value is the dielectric constant of each sample at 100 Hz.
[0054] Breakdown field strength test: Using RK2674A withstand voltage tester, place the multilayer composite film prepared in Examples 1 to 3 and Comparative Example 1 between two electrodes, immerse the electrodes and the film in insulating oil (dimethyl silicone oil), continuously increase the voltage until the voltage value drops instantly, and record the maximum voltage. The ratio of the maximum voltage to the film thickness is the breakdown field strength value.
[0055] Although the embodiments disclosed in the present invention are as above, the contents described are only embodiments adopted to facilitate understanding of the present invention and are not intended to limit the present invention. Any technician in the field to which the present invention belongs can make any modifications and changes in the form and details of implementation without departing from the spirit and scope disclosed in the present invention, but the scope of patent protection of the present invention shall still be subject to the scope defined in the attached claims.
[0056] Compared with the prior art, the present invention uses a polymer polyimide having high breakdown strength and high temperature resistance as the base film; the second layer is a high insulation nanosheet and a polymer adhesive, which connects the upper and lower polymer films, constructs a multilayer structure, and hinders the extension of the breakdown path, while also hindering the transfer of carriers and suppressing conduction losses. Therefore, the polymer multilayer composite film provided by the present invention has a good application prospect in the field of capacitor energy storage.
Claims
1. A double-layer composite film, characterized in that: The double-layer film comprises: a first layer of polyimide composite film and a second layer of adhesive film.
2. The polyimide composite film according to claim 1, characterized in that: The high dielectric nanoparticles are barium titanate, titanium dioxide, barium strontium titanate, and calcium copper titanate.
3. The double-layer composite film according to claim 1, characterized in that: The second film is composed of insulating nanosheets and a polymer adhesive.
4. The multilayer composite film according to claim 3, characterized in that: The insulating nanosheets are one or more of boron nitride, aluminum oxide, mica, and montmorillonite.
5. The multilayer composite film according to claim 3, characterized in that: The second layer of polymer adhesive is one or more of low-viscosity epoxy adhesive and polydimethylsiloxane.
6. The multilayer composite film according to any one of claims 1 to 5, characterized in that The thickness of the polyimide composite film is 5 μm-15 μm.
7. The multilayer composite film according to any one of claims 1 to 5, characterized in that The thickness of the second layer is 0.5 μm-5 μm.
8. The method for preparing a double-layer composite film according to any one of claims 1 to 7, characterized in that: The following steps are involved: The first step is the preparation of high dielectric nanoparticle / polyimide composite film; A certain amount of high dielectric nanoparticles is added to an organic solvent A for ultrasonic dispersion to obtain a uniform mixed solution B; after adding ODA, the mixture is stirred evenly and then ultrasonicated for 1 hour, and finally PMDA is added for stirring and reaction to obtain a mixed solution C, the mixed solution is placed in a vacuum drying oven to evacuate the vacuum, the solution is poured onto a glass plate and coated with a scraper to form a thin film, and finally placed in an electric constant temperature blast drying oven and set to 130°1h, 180°1h, 230°1h, 280°1h, 300°0.5h, and run the drying and curing procedures; the obtained film thickness is between 5-15μm; Step 2: Preparation of double-layer film: A certain mass of insulating nanosheet powder is ultrasonically dispersed in an organic solvent D to obtain a uniform mixed solution E. A certain mass of adhesive component a is then added to solution E, and after ultrasonic dispersion, a fixed proportion of adhesive component b is added, and ultrasonic dispersion is continued until uniform dispersion, and the solvent is heated and stirred continuously to evaporate, and the mixture is placed in a vacuum drying oven for evacuation to obtain a mixed solution F; a polymer film is spread flat on a clean glass plate, a certain volume of the above solution F is added dropwise on the surface of the film, and the solution is evenly coated on the bottom polymer film by a casting method to obtain a double-layer film, which is then placed in an oven at 50-80°C for curing for 24 hours.
9. The preparation method according to claim 8, characterized in that: In the first step, the organic solvent A is one of isopropanol, dimethylacetamide and N-methylpyrrolidone.
10. The preparation method according to claim 8, characterized in that: In the second step, the size of the insulating nanosheets is 2-15 μm.
11. The preparation method according to claim 8, characterized in that: In the second step, the organic solvent D is one of acetone and tetrahydrofuran.
12. The preparation method according to claim 8, characterized in that: The vacuum degassing time is 5 to 15 minutes.